The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1017/s1366728905002373
|View full text |Cite
|
Sign up to set email alerts
|

Sentence interpretation strategies in emergent bilingual children and adults

Abstract: This study examined sentence processing in emergent bilingual children and young adults in both and . One hundred participants from five different age groups (5;4-7;11, 8;0-10;11, 11;2-13;11, 14;0-16;8 years, and college-age adults)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 40 publications
(74 reference statements)
1
41
0
Order By: Relevance
“…Hernandez, Bates and Avila (1994) reported data to suggest that highly proficient adult bilinguals amalgamate cue-based processing strategies from both languages. Reyes and Hernandez (2006) reported similar amalgamated strategies in Spanish–English bilingual children. Specifically, they showed that the Spanish–English children began attending to subject-verb agreement as a cue to interpretation later than monolingual Spanish children but earlier than monolingual English children, and were delayed overall in their use of word order to interpret non-canonical sentences (e.g., the dog the horse is chasing and is chasing the dog the horse , in which monolingual speakers of both languages typically interpret the second NP as the agent).…”
Section: Discussionmentioning
confidence: 86%
“…Hernandez, Bates and Avila (1994) reported data to suggest that highly proficient adult bilinguals amalgamate cue-based processing strategies from both languages. Reyes and Hernandez (2006) reported similar amalgamated strategies in Spanish–English bilingual children. Specifically, they showed that the Spanish–English children began attending to subject-verb agreement as a cue to interpretation later than monolingual Spanish children but earlier than monolingual English children, and were delayed overall in their use of word order to interpret non-canonical sentences (e.g., the dog the horse is chasing and is chasing the dog the horse , in which monolingual speakers of both languages typically interpret the second NP as the agent).…”
Section: Discussionmentioning
confidence: 86%
“…Proficiency can be established through performance on test batteries designed specifically for that purpose such as the Woodcock–Muñoz Language Survey – Revised (Woodcock, Muñoz-Sandoval, Ruef & Alvarado, 2005) or tests of general language ability like the Peabody Picture Vocabulary Test (Dunn & Dunn, 1997; e.g., Bialystok & Viswanathan, 2009; Reyes & Hernández, 2006; Vagh, Pan & Mancilla-Martinez, 2009). Researcher-designed proficiency batteries (Dunn, Padilla, Lugo & Dunn, 1986) are also sometimes used to establish proficiency in particular domains such as grammar (Jia et al, 2002) or word learning (Kan & Kohnert, 2005) where tests are unavailable in the target language or unsuitable for the desired task.…”
Section: Tests Of Language Proficiency and Dominancementioning
confidence: 99%
“…3. Cue-use patterns: Based on the initial pattern of amalgamation in Pham and Kohnert (2010) as well as the cross-sectional results of Hernandez and Reyes (2006), we predict that at the group level, participants will continue to rely on an amalgamated set of cues rather than differentiated cues for each language. Consistent with previous studies with bilinguals (Liu, Bates, & Li, 1992;Pham & Kohnert, 2010), we also anticipated individual-level variability in which individual children will show various patterns of forward or backward transfer, amalgamation or differentiation.…”
Section: Study Purpose and Predictionsmentioning
confidence: 99%